2020
DOI: 10.1002/pc.25765
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterizations of ultra‐high molecular weight EPDM/PP based TPV nanocomposites for automotive applications

Abstract: This research article reports, the preparation of thermoplastic vulcanizates (TPVs) and TPV nanocomposites (TPVNs) based on EPDM and polypropylene (PP). New generation ultra-high molecular weight EPDM (UHMW-EPDM) and PP with nano-fillers (nano-clay and nano-silica) and has been studied and characterized extensively typically for automotive applications. This special type of UHM-EPDM-based TPVs exhibit superior physico-mechanical properties over conventional EPDM-based TPVs and in the presence of nano-fillers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…It is observed for all the samples, degradation temperature range is all most same for all the TPV samples, which is from 490 to 500°C. [ 38–42 ] In the TSSR study, the best thermomechanical property has been found for ZMA, then ZDMA, and followed by the other co‐agents. It is also identified that the TGA result and TSSR result follow the same tendency.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed for all the samples, degradation temperature range is all most same for all the TPV samples, which is from 490 to 500°C. [ 38–42 ] In the TSSR study, the best thermomechanical property has been found for ZMA, then ZDMA, and followed by the other co‐agents. It is also identified that the TGA result and TSSR result follow the same tendency.…”
Section: Resultsmentioning
confidence: 99%
“…Based on developments in Daw Chemicals catalyst technology, novel grades of EPDM, i.e., ultrahigh molecular weight EPDM, known as (UHMW)NORDEL™ were developed. NORDEL is highly efficient in producing thermoplastic vulcanizates (TPVs), light color home appliance gaskets, and black color low hardness molded articles [33,34].…”
Section: α-Olefin (Co)polymersmentioning
confidence: 99%
“…The Formula (9) shows that the internal energy of PNB changes slowly in the tensile process [29]. It is assumed that there are no intramolecular and intermolecular forces in PNB, and the internal energy of the system remains unchanged when the elastomer deforms.…”
Section: Shape Memory Performancementioning
confidence: 99%